The Relationship Between Organizational Culture Knowledgemanagement and Innovation Performance in High-Tech Enterprises - Bo , Wang; Zhongwu, Li (Journal of Roi Kaensarn Academi, 2024)
Focusing on innovation performance in high-tech enterprises, analyzing the influencing factors, and modeling and verifying the two crucial factors of organizational culture and knowledge management among many factors affecting innovation performance, effective strategies and recommendations can be provided for enhancing technological innovation performance. The objectives of this research were to study investigates the relationship between organizational culture, knowledge management, and innovation performance in high-tech enterprises based on the organizational culture model and two-dimensional knowledge management model within the dual S-cube framework. The research method was a mixed method, including qualitative research and quantitative research. The sample was 620 people from population of this study includes national-level high-tech enterprise parks in China, This study used purposive sampling method, using the snowball method. Obtained by purposive sampling method. The instruments used for data collection was five-point rating scale questionnaires form. Statistics used for data analysis included frequency, percentage, mean, Standard Deviation, Confirmatory Factor Analysis, and Structural Equation Model was employed. Research findings were: 1)This research explores the interplay between organizational culture, knowledge management practices, and innovation performance within high-tech enterprises. It investigates how organizational culture influences knowledge management processes and subsequently affects innovation outcomes. The study aims to provide insights into strategies that can enhance innovation performance through effective management of organizational culture and knowledge resources in high-tech settings.2) The different organizational cultures of enterprises, their knowledge management methods have different ways and means of affecting the innovation performance of the organization. 3) According to the above empirical results, although the effect of chain mediation is significant, due to the greater direct effects of collective organizational culture on codified knowledge management and fragmented organizational culture on Inter personalization knowledge management, combining codification. The correlation coefficients from centralized knowledge management and Inter personalization knowledge management to knowledge socialization, knowledge internalization, knowledge combination, and knowledge internalization.